Competency Analysis of Student Coqnitive in Learning in Elementary Schools - Fita Nelyza (Universitas Serambi Mekkah, 2021)
The principle of the guided inquiry learning process interaction emphasizes theinteraction between students and teachers, and between students and theenvironment. Learning as an interaction process means placing the teacher not as asource of learning, but as a regulator of the environment or regulator of theinteraction itself, the teacher as the questioner. The purpose of this study was todetermine how the effect of the guided inquiry model on improving student conitivecomptency. This research was conducted in the even semester of the 2017/2018academic year, using the pre-experimental design method through one group pretestposttest design. This research was carried out in three stages, namely: giving a pretestquestionnairetoobtaintheaveragescoreofstudentco-techniciancompetencies, implementing the guided inquiry learning model, and giving the final test (posttest)after learning. The subjects of this study were fourth grade students consisting of 14male students and 13 female students. The data collection techniques used wereobservation and tests. Observations were made to observe student activities, whilethe test consisted of preliminary and final tests used to measure learning success. Theassessment instrument consists of an observation sheet filled out by the observer andthe test questions consisting of 10 questions. Furthermore, student learning outcomesare processed using the Gain formula (g). Based on the research results obtained, 11students obtained a Gain value of 0.75 in the high category, and 16 students obtaineda Gain value of 0.60 in the moderate category. The overall average value of learningoutcomes is 0.65 in the medium category. Thus, it can be concluded that theapplication of the guided inquiry model can affect science student coqinitive.